The Role of BOPO in Mediating the Effect of RGEC on the Financial Health of Islamic Banks after the COVID-19 Pandemic - Widodo, Nabilah Febriyane Prasetyo; Ramdani, Ramdani (Journal of Applied Islamic Economics and Finance, 2025)
The COVID-19 pandemic has placed considerable pressure on the economic sector, including Islamic banking. During the recovery phase, operational efficiency and strong governance have become essential for ensuring resilience and long-term sustainability. This study examines the mediating role of the operational efficiency ratio (BOPO) in the relationship between RGEC components, namely Capital Adequacy Ratio (CAR), Good Corporate Governance (GCG), and Non-Performing Financing (NPF), to influence bank health, measured by Return on Assets (ROA). A quantitative approach was employed using Structural Equation Modeling (SEM) with the Warp-PLS technique, utilizing secondary data from Indonesian Islamic banks between 2021 and 2023. The findings indicate that BOPO significantly mediates the impact of CAR and NPF on ROA, while GCG shows no significant mediation effect. These results emphasize the strategic importance of improving operational efficiency to enhance profitability in Islamic banks post-pandemic and provide meaningful contributions to the academic discourse on Islamic financial management.